Analisis Strategi Pemasaran Ikan Hias di Bintang Farm Nagari Sunua Barat Kecamatan Nan Sabaris Kabupaten Padang Pariaman - Pretty Zinta; Rahmi Rahmi (ARZUSIN, 2026)
Marketing strategies have been the focus of various studies, but research that specifically discusses ornamental fish marketing strategies in local-scale businesses using the 7P marketing mix approach remains limited. This study aimed to analyze ornamental fish marketing strategies at Bintang Farm, Nan Sabaris Subdistrict, Padang Pariaman Regency. This study used a qualitative approach with a case study design, involving the business owner as the main informant selected through purposive sampling. Data were collected through interviews, observation, and documentation, and were then analyzed using qualitative descriptive analysis. The results showed that the marketing strategies implemented had not been optimal, as indicated by the low intensity of promotion through social media, limited availability of natural feed that affected product quality, and sales fluctuations over time. These findings contribute to the development of marketing strategy studies, particularly the application of the 7P marketing mix in local-scale ornamental fish businesses, while also broadening understanding of the relationship between product quality, promotion, and marketing effectiveness. The conclusion of this study confirms the importance of optimizing digital promotion, improving product quality, and managing more integrated marketing strategies to support the sustainability of ornamental fish businesses. The implications of this study provide practical guidance for business actors in designing more effective marketing strategies and open opportunities for further studies on the effectiveness of digital marketing and the integration of production aspects in fisheries business marketing.